Play – Education – Development and Discovery of The World Around - Oybek Kakhramonovich Mirzorakhimov (Euro Asian Journal Publishing, 2024)
The article provides information about the role of play in early preschool age, through which they are raised and developed. About the full-fledged skill of the game, about the fact that the acquisition of new knowledge in the game is much more successful than in training sessions. Play is one of the indicators of the overall development of a child’s level of cognitive activity.
Keywords: Child; game; hobbies